Introducing the individual Teamwork Observation and Feedback Tool (iTOFT): Development and description of a new interprofessional teamwork measure. Issue 4 (3rd July 2016) - Thistlethwaite, Jill; Dallest, Kathy; Moran, Monica; Dunston, Roger; Roberts, Chris; Eley, Diann; Bogossian, Fiona; Forman, Dawn; Bainbridge, Lesley; Drynan, Donna; Fyfe, Sue
ABSTRACT: The individual Teamwork Observation and Feedback Tool (iTOFT) was devised by a consortium of seven universities in recognition of the need for a means of observing and giving feedback to individual learners undertaking an interprofessional teamwork task. It was developed through a literature review of the existing teamwork assessment tools, a discussion of accreditation standards for the health professions, Delphi consultation and field-testing with an emphasis on its feasibility and acceptability for formative assessment. There are two versions: the Basic tool is for use with students who have little clinical teamwork experience and lists 11 observable behaviours under two headings: 'shared decision making' and 'working in a team'. The Advanced version is for senior students and junior health professionals and has 10 observable behaviours under four headings: 'shared decision making', 'working in a team', 'leadership', and 'patient safety'. Both versions include a comprehensive scale and item descriptors. Further testing is required to focus on its validity and educational impact.